Inkjet-printed electrode modified with magnetite particles and carbon nanotubes for the non-enzymatic amperometric determination of hydrogen peroxide - Mass, M. I. (2022)
Fil: Mass, M. I. Instituto Nacional de Tecnología Industrial. Gerencia Operativa de Desarrollo Tecnológico e Innovación. Subgerencia Operativa de Áreas de Conocimiento. Dirección Técnica de Micro y Nano Tecnologías (INTI-GODTeI-SOAC); Argentina